Chapter 18 Re-imagining Politics through the Lens of the Commons - Bollier, David (Taylor & Francis, 2019)
In this wide-ranging and multidisciplinary volume, leading scholars, activists, journalists, and public figures deliberate about the creative and critical potential of public imagination in an era paradoxically marked by intensifying globalization and resurgent nationalism. Divided into five sections, these essays explore the social, political, and cultural role of imagination and civic engagement, offering cogent, ingenious reflections that stand in stark contrast to the often grim rhetoric of our era. Short and succinct, the essays engage with an interconnected ensemble of themes and issues while also providing insights into the specific geographical and social dynamics of each author's national or regional context.